THE EFFECT OF NONI (Morinda citrifolia) EXTRACT TO HEPAR HISTOPATHOLOGY AND TRIGLYCERIDE LEVEL IN RATS (Rattus Norvegicus) INDUCED BY DISLIPIDEMIA - Jhouharotul Faradisah; Diah Purwaningsari (Universitas Merdeka Madiun, 2019)
Dyslipidemia is an abnormal lipid metabolism which may cause fat degeneration on hepatocytes cells and elevated triglyceride serum level. Dyslipidemia can be prevented by the consumption of high antioxidant food. Noni(Morinda citrifolia) contains many antioxidant such as flavanoid, kuersetin, tannin, and saponin, which are able to prohibit the elevation of ROS.This research is aimed to find out the effect of noni(Morinda citrifolia) extract in reducing the number of hepatocyte’s cells with fat degeneration and decreasing the triglyceride level which is elevated due to high cholesterol diet induction.In this study white rats divided randomly into 4 groups, control group (K-), high cholesterol diet induced group (K+), high cholesterol diet induced with 100 mg/Kg BW noni extract group (P1), high cholesterol diet induced with 200 mg/Kg BW noni extract group (P2). The result shows that noni extract with dose 100 mg/Kg BW and 200 mg/Kg BWcan reduce the number of hepatocytes cells with fat degeneration (p= 0,026 and p=0,027) and decrease the level of triglyceride serum (p=0,036 and p=0,010).The conclusion is noni extract with dose 100 mg/KgBW reduces effectively the number of hepatocyte’s cells with fat degeneration and decreases the level of triglyceride serum which increase because of high cholesterol diet.